2015
DOI: 10.1155/2015/934367
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Analysis of MHD Water Functionalized Carbon Nanotube Flow over a Static/Moving Wedge

Abstract: The MHD flow and heat transfer from water functionalized CNTs over a static/moving wedge are studied numerically. Thermal conductivity and viscosity of both single and multiple wall carbon nanotubes (CNTs) within a base fluid (water) of similar volume are investigated to determine the impact of these properties on thermofluid performance. The governing partial differential equations are converted into nonlinear, ordinary, and coupled differential equations and are solved using an implicit finite difference met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Later, he extended his work by incorporating varying heat source [21]. Khan et al [22] explored the heat transfer impact past a moving wedge. Reddy et al [23] studied the MHD flow past non-linear stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Later, he extended his work by incorporating varying heat source [21]. Khan et al [22] explored the heat transfer impact past a moving wedge. Reddy et al [23] studied the MHD flow past non-linear stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Karami et al focused on new applications of carbon nanotubes on low‐temperature and direct absorption in solar collectors. Khan et al provided the numerical solutions of water‐MWCNT and water‐SWCNT based nanofluid flow over static/moving wedge and noticed an elevation in the values of rates of heat transfer and rates of velocity as magnetic field parameter rises. Haq et al investigated MHD flow and heat transfer of SWCNTs and MWCNTs with base fluids as (engine oil, water, and ethylene glycol) over stretching sheet and revealed that the values of Nusselt number and rates of velocity is higher in engine oil‐based CNTs than the ethylene glycol‐based CNTs. Sabiha et al theoretically examined specific heat, viscosity, and thermal conductivity of SWCNT with water‐based nanofluids in presence of sodium dodecyl sulfate with volume concentrations (0.05%–0.25%) and found that the thermal conductivity is maximum enhanced of 36.39% compared with water for 0.25%.…”
Section: Introductionmentioning
confidence: 99%
“…Hussanan et al [11] examined the e ect of some nano uids on accelerated plate with magnetic eld and a porous medium. The water functionalized carbon nanotube ow was analyzed over a moving/static wedge in the magnetic eld by Khan et al [12]. Haq et al [13] explored the e ects of magnetic eld with water functionalized metallic nanoparticles for squeezed ow over a sensor surface.…”
Section: Introductionmentioning
confidence: 99%